BMI changes in pediatric type 1 narcolepsy under sodium oxybate treatment. Issue 7 (3rd January 2021) - Ponziani, Virginia; Pizza, Fabio; Zenesini, Corrado; Vignatelli, Luca; Pession, Andrea; Plazzi, Giuseppe
Abstract: Pediatric type 1 narcolepsy (NT1) is often associated with overweight and obesity. Sodium oxybate (SO), approved for the treatment of narcolepsy with cataplexy from the age of 7 years old in the United States, has been associated with weight loss, although longitudinal pediatric studies are lacking. We report a retrospective cohort of 129 consecutive patients with a 4-year follow-up, to analyze the impact of different pharmacological treatments on body mass index (BMI) z -score. At baseline, the prevalence of obesity and overweight was 26.4% (34/129) and 29.5% (38/129), respectively. Patients were divided into three groups: children treated with SO alone (group 1), with SO-combined therapy (group 2), and without SO (group 3). At the end of the first year of follow-up, group 1 and group 2 showed a significant BMI z -score reduction compared to baseline: from 1.2 ± 1.1 to 0.4 ± 1.4 for group 1 ( p < 0.001), and from 1.4 ± 1.1 to 1 ± 1.3 for group 2 ( p = 0.002), independently from baseline clinical features. In the second year, only group 2 experienced a further and significant BMI z -score decrease (from 1.0 ± 1.2 to 0.6 ± 1.2, p = 0.037). No further significant BMI z -score changes were observed in SO-treated patients in the following years. Instead, children treated without SO developed a significant weight increase between the second and third year of therapy (BMI z -score from 0.3 ± 0.9 to 0.5 ± 0.9). In conclusion, SO treatment in pediatric NT1 is associated with a favorable weight reduction in the first year of treatment.